7.1k views
0 votes
6=4x+2y
-19=4x-3y
using elimination process

User MysteRious
by
5.3k points

2 Answers

2 votes
The answer is x= -1
y= 5
User Miguel Hernandez
by
5.5k points
3 votes

Answer: x= -1 , y= 5

Explanation:

6=4x+2y .........eq 1

-19=4x-3y .........eq 2

Subtracting eq 2 from eq 1

6=4x+2y

-

-19=4x-3y

This gives;

25=5y

divide both sides by 5

y=5

Substituting the value of y in eq 1

6=4x +2(5)

6=4x + 10

Subtract 10 from both sides

6-10=4x+10-10

-4=4x+0

-4=4x

Divide both sides by 4

-1=x

Therefore, x= -1

Verify the values of x and y in either of the equations, Let's use equation 1

6 =4(-1) +2(5)

6= -4 + 10

Hence, X= -1 and y = 5

User Chris Wilson
by
5.5k points